PENGARUH AKUNTANSI KONSERVATIF, UKURAN PERUSAHAAN, DAN DEFAULT RISK TERHADAP KOEFISIEN RESPON LABA (ERC) - Yossi Diantimala (Jurnal Telaah dan Riset Akuntansi, 2008)
This study aims to test the influence of conservative accounting, Company Size, and the default risk of Koefisien Respon Laba. Earnings Response Coefficient. This research was conducted as a response to a specific profit and specificity of each company is affected by several factors, such as the application of conservative accounting, firm size, and default risk. The number of samples for research in 2006 as many as 30 companies and in 2007 as many as 44 companies, bringing the total sample in This research into 74 companies. Hypothesis testing is done by using t test and F test are analyzed with the model of multiple linear regression analysis.The results show that partial Conservative Accounting significant negative effect on profit Response Coefficient, which received Ha1. Company Size significant negative effect that receive ha2 ERC. Furthermore, D efault Risk has a significant negative effect on ERC, meaning ha3 acceptable. To test F, obtained by statistical calculation shows that conservative accounting, company size, and default risk affect ERC manufacturing companies listed in Indonesia Stock Exchange 2005-2007 observation period, thus this study received Ha4. Keywords: Conservative accounting, Company Size, Default Risk, and Earnings Response Coefficient